2011
DOI: 10.1016/j.cub.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of the Parasitic Plant Family Orobanchaceae Reveal Surprising Conservation of Chlorophyll Synthesis

Abstract: Parasitism in flowering plants has evolved at least 11 times [1]. Only one family, Orobanchaceae, comprises all major nutritional types of parasites: facultative, hemiparasitic (partially photosynthetic), and holoparasitic (nonphotosynthetic) [2]. Additionally, the family includes Lindenbergia, a nonparasitic genus sister to all parasitic Orobanchaceae [3-6]. Parasitic Orobanchaceae include species with severe economic impacts: Striga (witchweed), for example, affects over 50 million hectares of crops in sub-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 45 publications
9
88
0
Order By: Relevance
“…Their plastomes also show more genomic rearrangements than autotrophs and the facultative hemiparasites T. versicolor and Bartsia inaequalis (17). These results are further corroborated by gene expression data from aboveground tissue of S. hermonthica, which expresses nuclear genes for light harvesting and photosystems with lower abundance than T. versicolor (18). The relaxation of purifying selection in both photosynthesis and housekeeping genes (e.g., rpl, rps) (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Their plastomes also show more genomic rearrangements than autotrophs and the facultative hemiparasites T. versicolor and Bartsia inaequalis (17). These results are further corroborated by gene expression data from aboveground tissue of S. hermonthica, which expresses nuclear genes for light harvesting and photosystems with lower abundance than T. versicolor (18). The relaxation of purifying selection in both photosynthesis and housekeeping genes (e.g., rpl, rps) (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…1C). However, some studies showed that stems of different Cuscuta spp., including dodder, photosynthesize to varying degrees, consistent with other lineages of parasitic plants (Choudhury and Sahu, 1999;Revill et al, 2005;Wickett et al, 2011). Our differential gene expression analysis also showed high expression of photosynthetic genes in dodder seedlings.…”
Section: Increased Transporter Activity and Reduced Photosynthesis Wisupporting
confidence: 57%
“…Recently, de novo assembly and analysis of transcriptomes of root parasites, belonging to family Orobanchaceae, provided important insight into the process of parasitism, showing the association of photosynthesis-related genes and cell wall-modifying b-expansin in the process of parasitism (Wickett et al, 2011;Honaas et al, 2013). To understand the molecular mechanisms underlying dynamic morphological and functional changes in haustoria development, however, detailed transcriptional profiling along developmental stages of parasitism is necessary.…”
mentioning
confidence: 99%
“…Thus, the absence of ptDNA reads from Illumina sequencing data of four different Polytomella spp. is perplexing as is the absence of an obvious plastid gene expression system from P. parva transcriptomic data, especially given that transcriptome sequencing of other colorless algae has consistently uncovered such a system (Bozdech et al, 2003;Borza et al, 2005;Wickett et al, 2011). Nuclear genes encoding proteins involved in the replication, repair, or expression of ptDNA represent a significant proportion (.7%) of the predicted C. reinhardtii plastid proteome (Terashima et al, 2011).…”
Section: The Possibility Of Plastid Genome Lossmentioning
confidence: 99%